Iowa RBA, October 27, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for October 27, 1997. Highlights of the update include the continuation of the Eurasian Collared Doves as well as sightings of two immature Surf Scoters, a Red Crossbill, and a second year Lesser Black-backed Gull. Also of note were state wide reports of Pine Siskins after a yearlong absence as well as large numbers of Purple Finches and Red-breasted Nuthatches. Also included are handwritten notes for the next week's update with sightings of a female White-winged Crossbill, an estimated one thousand Tundra Swans, and 158 raptors observed on a hawk watch. Epson - sheet feed/flatbed